Literature Review: Intrauterine Device Terhadap Resiko Kanker Serviks - Wiwin Hindriyawati; Anugerah Destia Trisetyaningsih (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Based on Riskesdas data, the prevalence of cancer in Indonesia shows an increase from 1.4 per 1000 population in 2013 to 1.79 per 1000 population in 2018. According to data from the Global Burden of Cancer Study (Globocan) from the World Health Organization (WHO), cancer cases in Indonesia in 2020 reached 396,914 cases and total deaths were 234,511 cases(1) The type of contraception and duration of contraceptive use are also said to be risk factors for cervical cancer in women(2). Castellagué's research (2011) states that women who accept IUDs have a 50 percent risk of developing cervical cancer compared to those who do not use them(3). Objective: To determine the effect of intrauterine devices on the risk of cervical cancer.Research Method: Literatures review The database search used was Google Scholar. A search for full text publication articles, Pubmed, Google Scholar from 2017 to 2022. A total of 7 journals were reviewed, including 7 full text Google Scholar S: 3 andPubmend: 4 journals. Characteristics of full text articles are discussed based on the quality of the article using critical appraisal research tools Hawker, S. et al. Results: Observing and measuring the quality of full text research journals on IUDs on the risk of cervical cancer, full text journals reviewed case control study methods, randomize control clinical trials, retrospective cohort analysis, cross sectional studies based on the conditions cohort study, retrospective cohort . based on the grade of Grade A articles there is 6 journal, Grade B there are 1 journals, based on country the journals come from California 1, Colombia 1, Denmark 1, Brazil 1, Indonesia 3.Conclusion: Copper IUD use was not associated with pre-cancer or cancer. and that IUD use reduces the incidence of cervical cancer. LNG-IUD use was associated with CIN2+ but not CIN3+. Because CIN2 is in the low level spectrum.Keywords: Intrauterine Device (IUD), Risk of Cervical Cancer